Handbook of career studies - Gunz, Hugh.; Peiperl, Maury; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2007)
This handbook will provide a comprehensive understanding about the latest findings and issues in career studies for researchers in the fields of industrial and organisational studies, human resources, organisational psychology and educational counseling.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Work -- Philosophy; Career development; Occupations; Psychology, Industrial; Electronic books